Cambodia - Intergovernmental Fiscal Architecture Study - World Bank (Washington, DC, 2022)
The Royal Government of Cambodia (RGC) has made a strong commitment to strengthening public service delivery through three interrelated public sector reform initiatives: Public Financial Management Reform Program (PFMRP), National Program for Public Administration Reform (NPAR), and Decentralization and Deconcentration (D and D) reforms. D and D reforms began at the commune and sangkat (CS) level, the lowest tier of sub-national administrations (SNAs), with the direct election of CS councils in 2002. This study reviews the recent changes in Cambodia’s intergovernmental fiscal architecture. It starts with the description of the overall sub-national system, then delves into the challenges of managing different aspects of the reform, such as assigning expenditure responsibilities and financing sources. It also assesses the strengths and weaknesses of the public financial management systems at the sub-national levels. The emphasis is at the district and municipality (DM) level, where more service delivery functions and resources are expected to be transferred. The research is based on an extensive review of government documents and regulatory framework, quantitative data analysis, and fieldwork conducted in March 2020. Drawing on its findings, the study offers policy recommendations on how the country’s inter-governmental fiscal architecture can be improved over the short and long-term horizons.